Anti-proliferative and anti-apoptotic effects of grape seed extract on chemo-resistant OVCAR-3 ovarian cancer cells - Mansour Homayoun; Reza Ghasemnezhad Targhi; Mitra Soleimani (Wolters Kluwer Medknow Publications, 2020)
Background and purpose: Ovarian cancer is the deadliest cancer in women. The main challenge in the inhibition of ovarian cancer cells is chemo-resistance. Seeking to overcome this issue, several strategies have been suggested, including the administration of natural products. Grape seed extract (GSE) is a good source of polyphenols and its anticancer effects have been reported by many studies. In this study we aimed to evaluate the effects of GSE on OVCAR-3, a chemo-resistant ovarian cancer line. Experimental approach: OVCAR-3 cells were treated with GSE (71 μg/mL) for 24 and 48 h. Cell viability and cell apoptosis were measured by MTT and flow cytometry. The real-time polymerase chain reaction was used to determine the expression of genes involved in the cell cycle (PTEN, DACT1, AKT, MTOR, GSK3B, C-MYC, CCND1, and CDK4) and apoptosis (BAX, BCl2, CASP3, 8 and 9). The expression of CASP3 protein was evaluated by the CASP3 assay. Findings / Results: The results showed that treatment of OVCAR-3 cells with GSE, increased the expression level of PTEN and DACT1 tumor suppressor genes, as well as apoptotic genes, CASP3, 8, and 9 (P < 0.001). Also, the induction of tumor suppressor genes expression was associated with an increase in the expression of BAX/BCL2 gene ratio as pro- and anti-apoptotic genes. The expression of the genes involved in the cell cycle, CCND1 and CDK4, was inhibited (P < 0.001). The results indicated that GSE induced cell apoptosis in a time-dependent manner (P < 0.001). Also, the GSE treatment resulted in the CASP3 protein expression (P < 0.001). Conclusion and implications: According to the results of this study, GSE may exert anti-tumorigenic effects on chemo-resistant OVCAR-3 ovarian cancer cells which might be mediated by the expression of tumor suppressor genes that interact with cell signaling pathways, cell cycle, and cell apoptosis. Hence, the consumption of GSE extract during chemotherapy may overcome part of chemo-resistance in ovarian cancer.